Abnormal Spatial Patterns of Intrinsic Brain Activity in Osteonecrosis of the Femoral Head: A Resting-State Functional Magnetic Resonance Imaging Study - Feng, Shengyi; Li, Bo; Li, Gang; Hua, Xuyun; Zhu, Bo; Li, Xuejia; Lu, Wenting; Xu, Jianguang (Frontiers in Human Neuroscience, 2020)
Background: Osteonecrosis of the femoral head (ONFH) is common in clinics, yet little is known about the properties and representation in the brain. We used resting state functional Magnetic Resonance Imaging (rs-fMRI) to investigate spatial patterns of spontaneous brain activity in ONFH patients. Methods: The study included ONFH patients and health controls.The pattern of intrinsic brain activity was measured by examining the amplitude of low-frequency fluctuations (ALFF) of blood oxygen level dependent signals of rs-fMRI. Meanwhiles,we also used Harris hip scores to measure the behavior performance of ONFH patients and health controls. Result: 10 ONFH patients and 10 health controls were investigated. We found global ALFF differences between two groups throughout the occipital, parietal, frontal, prefrontal, and temporal cortices. The brain regions in sensorimotor network, pain-related network and Emotion & Cognition network were found altered activity in ONFH patients. Specifically, the most signiﬁcant ALFF differences the groups appeared in the middle occipital gyrus, with a reduced pattern of activity when comparing healthy controls with ONFH patients. The correlation investigations also showed that the regions with ALFF changes had significant correlations with the behavior performance of patients as measured by Harris hip scores. Conclusions: Our study described the abnormal pattern of brain activity in ONFH patients and could be used for understanding the gait abnormality and intractable pain in the central level.